PENGARUH RASIO KEUANGAN DAN RASIO PROFITABILITAS TERHADAP PERUBAHAN LABA PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi, Mike Kusuma; Yames, Vina Oktavia (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to analyze the Effect of Financial Ratios and Profitability Ratios on Profit Growth in Property and Real Estate companies listed on the Indonesia Stock Exchange in 2018-2021. This type of research used is a quantitative method. The samples used were 60 companies. The technique used is purposive sampling. In analyzing the data using Eviews 10 software. The data analysis method used is panel data regression. Based on the results of the study, it shows that financial ratios have no effect on earnings changes and profitability ratios have a negative effect on earnings changes